Blockchain-Systeme für den manipulationssicheren Datenaustausch in der industriellen Fertigung: Distributed Ledgers für den Materialdatenaustausch - Lechner, Michael; Frey, Philipp; Kreß, Maximilian; Christ, T.; Charlet, C.; Merklein, Marion (wt Werkstattstechnik - Online, 2021)
Modern industrial manufacturing processes have to meet ever-increasing requirements in terms of material and resource efficiency, quality and product variety. The cross-company consolidation of integrity-secured data is a prerequisite for the retrospective identification of quality problems, the documentation of compliance with standards and the allocation of resource consumption along the value chain. This paper uses the example of a material characterization process for hybrid lightweight construction processes to discuss how blockchain technology can be used to implement a tamper-proof storage concept.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Digitalisierung; Industrie 4.0; Werkstoffe

Distributed Ledgers für den Materialdatenaustausch - Lechner, Michael; Frey, Philipp; Kreß, Maximilian; Christ, Tassilo; Charlet, Christoph; Merklein, Marion (wt Werkstattstechnik - Online, 2021)
Moderne industrielle Fertigungsprozesse müssen stetig wachsende Anforderungen an Material- und Ressourceneffizienz, Qualität und Variantenvielfalt erfüllen. Die unternehmensübergreifende Zusammenführung integritätsgesicherter Daten ist hierbei Voraussetzung für die retrospektive Identifikation von Qualitätsproblemen, die Dokumentation der Einhaltung von Standards und die Allokation von Ressourcenverbräuchen entlang der Wertschöpfungskette. In diesem Beitrag wird am Beispiel eines Materialcharakterisierungsverfahrens für den hybriden Leichtbau diskutiert, wie mit der Blockchain- Technologie ein manipulationssicheres Speicherkonzept umgesetzt werden kann.<br
Keywords: Werkstoffe; Digitalisierung; Industrie 4.0

Hybrid process chains combining metal additive manufacturing and forming – A review - Hafenecker, Jan; Bartels, Dominic; Kuball, Clara-Maria; Kreß, Maximilian; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (CIRP Journal of Manufacturing Science and Technology, 2023)
Mass production of customized parts using conventional manufacturing technologies is challenging. The increasing use of hybrid approaches is a promising way to address mass customization. Due to the widespread use of the term hybrid in manufacturing technologies, the amount of literature is increasing dramatically. Therefore, this paper aims to provide an overview of the current state of the art on the combination of additive manufacturing (AM) and metal forming. First, the term hybrid is classified, followed by examples of hybrid AM. The focus of this paper is on the combination of either sheet metal forming or bulk metal forming with either powder bed fusion or directed energy deposition. Examples of both sequences - AM before or after forming - are presented and analyzed for their potential use in hybrid parts. From the selected literature, the possibilities of this approach are derived as well as the ongoing need for future research. AM offers great potential for adjusting the microstructure and resulting material properties to improve formability. Furthermore, forming operations need to be adapted to the different material properties found in hybrid part
Keywords: Hybrid manufacturing Hybrid processes Hybrid parts Additive manufacturing Sheet metal forming Bulk metal forming Review paper

Material Characterization of Hybrid Components Manufactured by Laser-Based Directed Energy Deposition on Sheet Metal Substrates - Kreß, Maximilian; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (The 25th International Conference on Material Forming (ESAFORM 2022), 2022)
Laser-based directed energy deposition (DED-LB/M) allows the application of a wear-resistant metal coating to the surface of a sheet metal substrate. Subsequent deep drawing of the part enables high material efficiency, significantly shorter production times, and lower unit costs compared to, for example, solely machined production of the entire component. At the same time, energy-intensive global heat treatment strategies can be avoided. For the numerical analysis of such hybrid process chains, both the sheet metal substrate and the additively applied coating are usually characterized individually. However, the low thickness of the coating in combination with a relatively high welding depth, which is required for a good bond to the sheet metal substrate during subsequent forming, lead to a strong gradient of the mechanical properties as well as complex mechanical interactions in the bonding zone. Therefore, appropriate characterization methods are required. In this work, an investigation of different influencing factors, like the rolling, hatch and tensile direction, is carried out with the aid of tensile tests using hybrid specimens. In this way, interactions between the influencing factors are identified. As substrate, 3.5 mm thick 16MnCr5 blanks are used, with an approximately 0.68 mm thick coating of Bainidur® AM. In addition, an optical surface roughness measurement and metallographic analysis of the tensile specimen’s edge area after laser cutting is performed.<br
Keywords: directed energy deposition; sheet metal forming; material characterization; case hardening steel